The level of public awareness towards the benefits provided by SOCSO / Siti Nabilah Hussin - Hussin, Siti Nabilah (2011)
This research has been conducted meeting point on “The Level of Public Awareness toward Benefits Provided by SOCSO. Social Security Organization (SOCSO) plays an important role in order to ensure Malaysian’s welfare at the event of any accidents that related to their employment which may affect the public financial security. Here, the awareness toward benefits provided under SOCSO’s Schemes among public is very important. Most of public contributes to SOCSO because it is enforce by law. That perception need to be change by increase the public awareness towards SOCSO’s opportunities. SOCSO is committed to create a caring society under Employees’ Social Security Act 1969 by Human Resources Ministry. The main objectives of this research are (1) to discover the needs and benefits provided by SOCSO, (2) to determine the level of public awareness towards the benefits provided by SOCSO and (3) to determine the most contributing factors those contribute to the level of public awareness toward the benefits provided by SOCSO. There are 50 questionnaires was distributed to respondents who are non government employees at Bandaraya Kuala Terengganu. The researcher had used Purposive Sampling as the sampling technique. The process of analyzing and interpreting data has been presented with tables using method as reliability test, frequency and descriptive analysis. Several recommendations that can be taken into consideration have been come out by researcher at the end of this study. The researcher optimism that SOCSO may increase the public awareness toward the benefits provided by implement those recommendations.